2019
DOI: 10.1111/aor.13499
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of a novel organ perfusion technique: ex vivo normothermic perfusion of deceased donor kidneys

Abstract: Ex vivo normothermic perfusion (EVNP) technology is a promising means of organ preservation, assessment, and preconditioning prior to kidney transplantation, which has been pioneered by a single group. We describe the challenges of setting up clinical EVNP programs in 2 new centers, as well as early patient outcomes. Governance, training, and logistical pathways are described. In order to demonstrate safety and proficiency in this new technique, early patient outcomes are also described. Patient outcomes inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Thereby the actual static cold storage procedures on ice after flushing with crystalline solutions such as University of Wisconsin solution or Custodiol may be replaced in the future. In the last few years, clinical studies showed the advantage of warm machine perfusion after organ harvest to cold storage, either static or perfused [ 7 , 97 ]. This technique needs O 2 carriers to maintain the physiological status or to regenerate the tissue.…”
Section: Pfc-based Oxygen Carriers: Peculiarities and Fields Of Applimentioning
confidence: 99%
“…Thereby the actual static cold storage procedures on ice after flushing with crystalline solutions such as University of Wisconsin solution or Custodiol may be replaced in the future. In the last few years, clinical studies showed the advantage of warm machine perfusion after organ harvest to cold storage, either static or perfused [ 7 , 97 ]. This technique needs O 2 carriers to maintain the physiological status or to regenerate the tissue.…”
Section: Pfc-based Oxygen Carriers: Peculiarities and Fields Of Applimentioning
confidence: 99%
“…Pankaj Chandak et al of Guy’s and St Thomas’ Hospitals NHS Trust and King’s College London, London, United Kingdom reported on ex vivo normothermic perfusion (EVNP) in two centers. They described the challenges of setting up clinical EVNP programs, as well as early patient outcomes.…”
Section: Transplantation and Organ Preservationmentioning
confidence: 99%
“…Normothermic machine perfusion (NMP) is a method of organ preservation that facilitates restoration of cellular metabolism, reviving the organ ex vivo to resume normal physiological functions 7 . Over the last few years, a number of NMP techniques and commercially available devices have been adopted into clinical practice for kidney, heart, liver, and lung transplantation 8–10 . Kidney NMP was first described in 2008 11 .…”
Section: Introductionmentioning
confidence: 99%